The dimensional accuracy of provisional dental replacements made by different technologies - Kohan, Miroslav; Rajťúková, Viktória; Chromý, Ľuboš; Balint, Tomáš; Hudák, Radovan (Lékař a technika, 2024)
The accuracy and quality of temporary dentures are important factors in dentistry, especially when bridging the time between tooth preparation and the placement of definitive dentures. The aim of this study is to determine the dimensional accuracy of temporary dental prostheses, specifically crowns and bridges, manufactured using different technologies. Three manufacturing methods were evaluated: stereolithography (SLA), digital light processing (DLP) and CNC milling. A total of 30 temporaries (n = 30) were fabricated, with an equal number fabricated using each technology. The fabricated samples were scanned with an S900 Arti 3D scanner (Zirkonzahn, Italy) and the scanned data was analyzed using GOM Inspect software (Zeiss, Germany) to detect deviations from the original model. The results showed that SLA technology showed the smallest deviations (0.025 ± 0.002 mm), indicating the highest accuracy among the tested technologies. DLP technology demonstrated medium accuracy (0.052 ± 0.011 mm), exceeding CNC milling, but not reaching SLA accuracy. Conversely, CNC milling showed the largest deviations (0.106 ± 0.009 mm) and the lowest accuracy in the production of temporary dentures. Based on the accuracy of the produced crowns and bridges, the SLA technology is therefore considered the most suitable for the creation of temporary dentures. These findings underscore the potential of SLA technology in achieving higher precision in dental applications, while offering a reliable method to produce quality temporary dental restorations.